Method for preparing lithium ion battery negative electrode material based on biomass material
Through enzyme-catalyzed degradation and nitrogen-sulfur double-doping, the specific surface area and conductivity of the negative electrode materials of lithium-ion batteries are improved, and the problem of insufficient performance of traditional materials is solved, and higher electrochemical performance and stability are achieved. It is suitable for high-quality high-quality products. Performance lithium-ion battery applications.
Patent Information
- Application Number
- CN202411270019.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The negative electrode materials of traditional lithium-ion batteries have low specific surface area, poor conductivity, limited cycle stability and insufficient thermal stability, making it difficult to meet the needs of high-performance lithium-ion batteries.
Porous structural materials are generated by enzyme catalytic degradation, and nitrogen-sulfur double-doping reaction is carried out, combined with hydrothermal carbonization and heat treatment, to improve the degree of graphitization of the material, and enhance mechanical strength and electrical conductivity through surface modification.
It significantly improves the initial capacity, rate performance, cycle stability and thermal stability of the negative electrode material of lithium-ion battery, extends the service life of the battery, and is suitable for fast charging and discharging and high-speed magnification applications.
Smart Images

Figure CN119284893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a method for preparing negative electrode materials for lithium ion batteries based on biomass materials. Background Art
[0002] With the widespread application of lithium-ion batteries in portable electronic devices, electric vehicles, and energy storage systems, improving battery performance has become a key research direction. The performance of lithium-ion batteries is mainly affected by the positive and negative electrode materials, and the development and optimization of negative electrode materials are crucial to improving the overall performance of the battery. Traditional lithium-ion battery negative electrode materials, such as graphite, are difficult to meet the current demand for high energy density and fast charge and discharge capabilities due to their low specific capacity and limited rate performance.
[0003] In recent years, biomass materials have gradually attracted attention as a green and renewable carbon source material. After carbonization, biomass materials can be converted into carbon materials with high specific surface area and good conductivity, which are suitable as negative electrode materials for lithium-ion batteries. However, traditional biomass carbonization methods usually have problems such as insufficient specific surface area, poor conductivity, and limited cycle stability, which make it difficult to meet the requirements of high-performance lithium-ion batteries.
[0004] In order to improve these deficiencies, researchers have tried to introduce heterogeneous atom doping (such as nitrogen, sulfur, etc.) into carbon materials to improve the conductivity and electrochemical activity of the materials. In addition, further surface modification and structural optimization measures have also been applied to improve the mechanical strength and thermal stability of the materials. However, in the existing technology, the degree of optimization of carbonization and doping processes is limited, resulting in little room for improving material performance. At the same time, some processes are complex and energy-intensive, which does not meet the requirements of green manufacturing. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing anode materials for lithium-ion batteries based on biomass materials, which solves the problems of low specific surface area, poor conductivity, insufficient cycle stability and mechanical strength, and poor thermal stability of the cathode materials for lithium-ion batteries prepared from biomass materials in the prior art.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a negative electrode material for a lithium ion battery based on biomass materials comprises the following steps: Step 1: pre-treating the biomass material, including washing and drying, to remove impurities and moisture; Step 2: using cellulase to perform enzymatic degradation on the pretreated biomass material to generate a porous structure material with a high specific surface area; Step 3: performing a nitrogen-sulfur dual doping reaction in the degraded biomass material, including using urea and sodium thiosulfate as doping sources and catalyzing the reaction with nitrase at 40-60° C.; Step 4: placing the doped material in a hydrothermal reactor at 180° C. for carbonization treatment to generate a nitrogen-sulfur dual-doped carbon material; Step 5: The carbonized material is subjected to subsequent heat treatment at 700°C for 2 hours in a nitrogen atmosphere to increase the degree of graphitization of the material; Step 6: Modify the surface of the heat-treated material to form a conductive film to obtain a negative electrode material for a lithium-ion battery.
[0007] Preferably, the biomass material is bamboo chips, and before the pretreatment step, the bamboo chips undergo the following treatment steps: a) Wash the bamboo shavings at least three times with deionized water, each time for no less than 20 minutes, to remove sand, dust and other impurities in the bamboo shavings; b) The washed bamboo chips are dehydrated through a filter, and then the dehydrated bamboo chips are placed in a hot air circulation oven at 60° C. and dried for 12 hours until the moisture content of the bamboo chips drops below 5%.
[0008] Preferably, the cellulase-catalyzed degradation step comprises the following: a) preparing a 0.5% (w / w) cellulase solution, wherein the pH value of the solution is controlled between 5.5 and 6.5; b) mixing bamboo scraps and cellulase solution in a volume ratio of 1:1 to form a suspension, and performing an enzyme-catalyzed degradation reaction in a water bath at 30-40° C. for 24 hours; c) The suspension was stirred continuously at 300 rpm using a magnetic stirrer.
[0009] Preferably, the nitrogen-sulfur dual doping reaction comprises the following steps: a) Prepare 0.1 mol / L urea solution and 0.1 mol / L sodium thiosulfate solution, and mix the two solutions in a volume ratio of 1:1; b) mixing the mixed solution with the degraded bamboo shavings suspension at a volume ratio of 1:1, and adding 0.2% (w / w) nitrification enzyme to catalyze the decomposition of urea and release amino groups for nitrogen doping; c) performing a dual doping reaction at 40-60° C. for 12 hours, and maintaining a stirring speed of 200-300 rpm during the reaction to ensure uniformity of doping; d) After the reaction is completed, the suspension is quickly cooled to room temperature in an ice water bath and then washed with deionized water until the pH value of the washing solution is neutral.
[0010] Preferably, the hydrothermal carbonization step comprises the following: a) placing the biomass material after nitrogen-sulfur dual doping treatment in a hydrothermal reactor lined with high-purity polytetrafluoroethylene, adding deionized water so that the volume of water is 3-5 times the volume of the material; b) slowly raising the temperature of the reactor to 180°C at a rate of 5°C per minute and maintaining the temperature for 6 hours; c) After the reaction is completed, the heating source is turned off, the reactor is allowed to cool naturally to room temperature, the carbonized material is taken out, washed with deionized water until the filtrate is colorless and transparent, and dried in an oven at 80°C for 24 hours.
[0011] Preferably, the subsequent heat treatment step includes the following: a) Spread the dried material evenly in a quartz boat, place it in the heating zone of a tube furnace, and turn on nitrogen protection with a nitrogen flow rate of 200 mL / min; b) heating the material to 700°C at a heating rate of 5°C / min and maintaining it at this temperature for 2 hours; c) After the insulation is completed, cut off the heating source and continue to flow nitrogen until the furnace temperature drops to room temperature.
[0012] Preferably, the surface modification step comprises the following: a) soaking the heat-treated carbon material in a 0.01 M catechol solution at room temperature for 2 hours to form a conductive film; b) After soaking, take out the material and dry it in an oven at 100°C for 1 hour.
[0013] Preferably, the preparation steps of the electrode material include: a) mixing the heat-treated and surface-modified carbon material, Super P conductive carbon black and PVDF binder in a mass ratio of 8:1:1; b) adding N-methylpyrrolidone (NMP) to the mixture and stirring the mixture at a speed of 500 rpm for 12 hours using a high-speed stirrer until a uniform slurry is formed; c) using an automatic knife coater to evenly coat the slurry on a copper foil current collector with a thickness of 15 µm, and the coating thickness is controlled at 100 µm; d) The coated electrode was dried in a vacuum environment at 120°C for 12 h.
[0014] Preferably, the coated electrode sheet is processed by the following steps: a) using a hot press to press the electrode sheet at a pressure of 10 MPa for 2 minutes to obtain an electrode sheet with uniform thickness; b) Use a high-precision mold to cut the pressed electrode sheet into discs with a diameter of 14 mm.
[0015] The present invention provides a method for preparing anode materials for lithium-ion batteries based on biomass materials. It has the following beneficial effects: 1. The present invention effectively increases the specific surface area of biomass materials and generates a porous structure through an enzyme-catalyzed degradation process. This improvement provides more active sites for lithium ion embedding / de-embedding, thereby significantly improving the initial capacity and overall electrochemical performance of the negative electrode material.
[0016] 2. The present invention adopts nitrogen-sulfur dual doping technology, by doping nitrogen and sulfur elements into carbon materials, significantly improving the conductivity of the material. This improvement not only helps to improve the rate performance of the battery, so that it can maintain high capacity under high current charging and discharging conditions, but also improves the overall charging and discharging efficiency of the battery.
[0017] 3. The present invention significantly improves the graphitization degree and structural stability of the carbon material through optimized carbonization treatment and subsequent heat treatment steps. This allows the negative electrode material to maintain structural integrity and capacity stability during long-term charge and discharge cycles, thereby extending the service life of the battery.
[0018] 4. The present invention significantly enhances the mechanical strength of the negative electrode material through surface modification technology, especially the introduction of metal oxide nanoparticles. This improvement reduces the risk of material damage during battery assembly and use, and improves the reliability and service life of the battery.
[0019] 5. The present invention adds a double-layer carbonization treatment in the optimization process. Through the two carbonization processes, the conductivity and thermal stability of the material are further improved, and the capacity retention rate of the negative electrode material at high-rate discharge is significantly improved, making it more suitable for use in scenarios that require fast charging and discharging.
[0020] 6. The present invention ensures the structural stability of the material under high temperature conditions through an improved heat treatment process, and significantly improves the thermal stability of the negative electrode material. This feature enhances the safety of the battery, especially in a high-temperature working environment, and can effectively reduce the risk of thermal runaway. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example: Please refer to the attached drawings *-attached drawings *, an embodiment of the present invention provides a method for preparing a negative electrode material for a lithium ion battery based on biomass materials, comprising the following steps: Step 1: Selection and pretreatment of biomass materials Material selection: Bamboo chips are selected as biomass raw materials mainly because of their high carbon content, rich fiber structure, and good mechanical strength, which make them an ideal carbon source material.
[0024] Material washing: The selected bamboo chips are placed in a large-capacity washing tank and washed repeatedly with deionized water to ensure that impurities such as mud, dust, etc. on the surface and inside of the bamboo chips are completely removed.
[0025] The washing process should be carried out at least 3 times, each time lasting 20 minutes, and lightly stirred with a stirrer to increase washing efficiency.
[0026] Material drying: The washed bamboo chips are dehydrated with a filter and then transferred to a hot air circulation oven at 60°C for 12 hours or until the material reaches a constant weight. The goal is to control the moisture content of the bamboo chips below 5% to prevent excess moisture from being generated during subsequent processing, resulting in uneven reactions.
[0027] Step 2: Enzyme-catalyzed degradation Enzyme solution configuration: Prepare 0.5% (w / w) cellulase solution. Cellulase should be high-efficiency industrial grade products to ensure the efficiency of cellulose degradation. The pH value of the solution should be controlled between 5.5-6.5 to maintain the optimal activity of the enzyme.
[0028] Enzyme catalyzed reactions: The dried bamboo chips were prepared into a suspension at a ratio of 1 g bamboo chips / 10 mL deionized water, and then the cellulase solution was added to the suspension at a volume ratio of 1:1, and stirred thoroughly to ensure sufficient contact between the bamboo chips and the enzyme solution.
[0029] The reaction was carried out in a water bath at 30-40°C for 24 hours, which is the optimal reaction temperature of cellulase. During this period, a magnetic stirrer was used to continuously stir at a speed of 300 rpm to prevent bamboo chips from settling and affecting the uniformity of the reaction.
[0030] Reaction termination and material cleaning: After the reaction, 0.1 M NaOH solution was used to neutralize the reaction solution to a pH of 7.0 to terminate the activity of the enzyme. The degraded bamboo chips were then repeatedly washed with a large amount of deionized water to remove the enzyme and the byproducts produced by the reaction.
[0031] Step 3: Initial reaction of nitrogen-sulfur co-doping Solution configuration: Prepare 0.1 mol / L urea solution and 0.1 mol / L sodium thiosulfate solution. Urea is used as a nitrogen source and sodium thiosulfate is used as a sulfur source. The pH values of the solutions are adjusted to 6.0 and 7.5, respectively, to optimize the reaction conditions of the two doping sources.
[0032] Initial doping reaction: The enzyme-degraded bamboo shavings suspension was mixed with the above two solutions in a volume ratio of 1:1:1. 0.2% (w / w) nitrase was added to the mixed solution to catalyze the decomposition of urea and release amino groups, and the reaction was carried out at 40-60°C for 12 hours.
[0033] During the reaction, the stirring speed was maintained between 200-300 rpm to ensure that the bamboo chips were fully in contact with the solution and that nitrogen and sulfur atoms could be uniformly doped into the microporous structure of the bamboo chips.
[0034] Post-reaction treatment: After the reaction is completed, the suspension is immediately placed in an ice water bath and quickly cooled to room temperature to prevent excessive reaction of nitrogen and sulfur elements from causing damage to the material structure. After cooling, the bamboo chips are separated from the solution using a filter and repeatedly washed with deionized water until the filtrate is colorless and transparent to ensure that impurities and unreacted substances are completely removed.
[0035] Step 4: Low-temperature hydrothermal carbonization and doping enhancement Hydrothermal reactor preparation: Take out the pretreated bamboo shavings and transfer them to a high-purity polytetrafluoroethylene (PTFE)-lined hydrothermal reactor. Add enough deionized water to completely immerse the bamboo shavings. The volume of water should be 3-5 times the volume of the material to ensure the uniformity of the hydrothermal reaction.
[0036] Hydrothermal reaction: The reactor temperature was set to 180°C, sealed, and maintained at this temperature for 6 hours. The high temperature and high pressure environment in the hydrothermal reactor can further decompose the cellulose in the bamboo chips and form a carbonized structure doped with nitrogen and sulfur in the material.
[0037] The key to this process is to control the heating rate so that the temperature rises slowly to the set temperature at a rate of 5°C per minute to prevent the material from structural collapse due to sudden temperature changes.
[0038] Post-reaction treatment: After the reaction is completed, the heating source is turned off and the reactor is allowed to cool naturally to room temperature. Subsequently, the carbonized material is taken out and thoroughly washed with deionized water until the pH value of the washing liquid is close to neutral. The washed material is placed in an oven at 80°C for 24 hours to ensure that all water is evaporated.
[0039] Step 5: Heat treatment and microstructure optimization Heat treatment equipment preparation: Use a high-temperature tube furnace to heat treat the material. Spread the dried material evenly in a quartz boat and place it in the heating zone of the tube furnace. Turn on the nitrogen atmosphere protection, and control the nitrogen flow rate at 200 mL / min to ensure an inert atmosphere environment throughout the treatment process.
[0040] Heat treatment process: The temperature was slowly raised to 700°C at a rate of 5°C / min and maintained at this temperature for 2 hours. This process further carbonized the material, increased the degree of graphitization, and enhanced the material's electrical conductivity.
[0041] During the heat preservation process, keep the nitrogen flowing to prevent oxidation of the material surface and protect the microstructure of the material. After 2 hours, cut off the heating source and continue to flow nitrogen until the furnace temperature drops to room temperature to ensure slow cooling of the material and avoid structural damage caused by thermal stress.
[0042] Surface modification: The heat-treated material was taken out and cooled to room temperature. The material was placed in a 0.01 M catechol solution and soaked at room temperature for 2 hours to allow a thin film with excellent conductivity to be adsorbed on the surface of the material.
[0043] After the adsorption was completed, the material was taken out, the surface solution was gently shaken off, and dried in an oven at 100 °C for 1 h to ensure the stable attachment of the modified film.
[0044] Step 6: Preparation and Forming of Electrode Materials Slurry preparation: The modified carbon material, Super P conductive carbon black and PVDF binder were mixed in a mass ratio of 8:1:1. NMP solvent was added and the mixture was stirred to a uniform slurry state at a stirring speed of 500 rpm for 12 hours to ensure the uniformity and fluidity of the slurry.
[0045] Electrode coating: The slurry was coated on a copper foil current collector with a thickness of 15 µm, and the coating thickness was controlled to 100 µm using an automatic knife coater. The coating process should be carried out in a clean room to avoid contamination by impurities.
[0046] The coated copper foil was dried in a vacuum oven at 120 °C for 12 h to ensure that the NMP solvent was completely evaporated to obtain a dry and uniform electrode sheet.
[0047] Tableting and cutting: The dried electrode sheets were pressed by a hot press with the pressure set at 10 MPa and the pressing time set at 2 minutes to obtain electrode sheets with uniform thickness and appropriate density.
[0048] After pressing, the electrode sheets are cut into discs with a diameter of 14 mm. High-precision molds should be used for cutting to ensure the dimensional consistency of the electrode sheets in preparation for battery assembly.
[0049] Step 7: Assembly and performance test of button battery Button battery assembly: In a glove box (maintaining an argon atmosphere with a water and oxygen content below 1 ppm), the prepared negative electrode sheet and lithium foil were assembled. A 1 M LiPF6 EC / DMC (1:1, v / v) solution was used as the electrolyte, and a glass fiber membrane was used as the separator to complete the assembly of the CR2032 button cell.
[0050] Electrochemical performance test: Cyclic voltammetry: CV tests were performed in the potential range of 2.5 V-0.01 V at a scan rate of 0.1 mV / s to evaluate the redox behavior and electrochemical reversibility of the material.
[0051] Constant current charge and discharge test: Constant current charge and discharge cycles were performed at 0.1 C, and the initial capacity was recorded. Subsequently, discharge tests were performed at 0.5 C, 1 C, and 2 C rates to evaluate the rate performance of the material.
[0052] Electrochemical impedance spectroscopy test: The test frequency range is 0.01 Hz to 100 kHz, analyzing the impedance characteristics of the electrode material, with a special focus on the interface resistance and charge transfer resistance to evaluate the conductivity and ion diffusion resistance of the electrode material.
[0053] Embodiment 2: The present invention provides a method for preparing a negative electrode material for a lithium ion battery based on biomass materials, comprising the following steps: Pretreatment of biomass materials: Bamboo chips were selected as biomass raw materials, and were washed and dried. The washing steps were the same as in the previous embodiment, i.e., the bamboo chips were washed with deionized water and dried until the moisture content was less than 5%.
[0054] Enzyme-catalyzed degradation: Prepare a 0.5% (w / w) cellulase solution with a pH value between 5.5 and 6.5. Mix bamboo shavings and the cellulase solution in a 1:1 volume ratio and perform enzyme-catalyzed degradation reaction at 30-40°C for 24 hours with continuous stirring.
[0055] Nitrogen-sulfur dual doping reaction: Prepare 0.1 mol / L urea solution and 0.1 mol / L sodium thiosulfate solution, mix them in a 1:1 volume ratio, mix them with the degraded bamboo chip suspension, add 0.2% (w / w) nitrase to catalyze, and react for 12 hours.
[0056] Hydrothermal carbonization treatment: The doped bamboo chips were placed in a polytetrafluoroethylene-lined hydrothermal reactor, deionized water was added, the temperature was raised to 180°C, and the reaction was carried out for 6 hours. After cooling, the materials were washed and dried.
[0057] Subsequent heat treatment: The material was evenly spread in a quartz boat, placed in a tube furnace, heated to 700°C with a nitrogen flow rate of 200 mL / min, maintained for 2 hours, and then cooled naturally to room temperature.
[0058] Surface modification: The heat-treated material was immersed in a 0.01 M catechol solution containing metal oxide nanoparticles (such as TiO2 or Al2O3) at a concentration of 2 wt% and treated under ultrasonic conditions for 30 min to ensure that the nanoparticles were evenly distributed on the surface of the carbon material.
[0059] After immersion, the material was taken out, the surface solution was gently shaken off, and dried in an oven at 120 °C for 1 h to ensure stable adhesion of the modified film to the metal oxide.
[0060] This embodiment improves the conductivity, cycle stability and mechanical strength of the carbon material by introducing metal oxide nanoparticles, and is particularly suitable for lithium-ion batteries in long-term cyclic use, effectively extending the service life of the battery. On the basis of the previous embodiment, the conductivity and cycle stability of the material are enhanced by introducing metal oxide nanoparticles, and the surface modification step is optimized.
[0061] Embodiment three: The present invention provides a method for preparing a negative electrode material for a lithium ion battery based on biomass materials. On the basis of the above-mentioned embodiments, the carbonization treatment step is further optimized, and the graphitization degree and the conductive performance of the carbon material are improved by a double-layer carbonization treatment process, comprising the following steps: Pretreatment of biomass materials: Bamboo chips are selected as biomass raw materials, and are washed and dried. The washing steps are the same as in the previous embodiment to ensure that impurities in the bamboo chips are fully removed.
[0062] Enzyme-catalyzed degradation: Prepare a 0.5% (w / w) cellulase solution with a pH value between 5.5 and 6.5. Mix bamboo shavings and the cellulase solution in a 1:1 volume ratio and perform enzyme-catalyzed degradation reaction at 30-40°C for 24 hours with continuous stirring.
[0063] Nitrogen-sulfur dual doping reaction: Prepare 0.1 mol / L urea solution and 0.1 mol / L sodium thiosulfate solution, mix them in a 1:1 volume ratio, mix them with the degraded bamboo chip suspension, add 0.2% (w / w) nitrase to catalyze, and react for 12 hours.
[0064] First carbonization treatment: The doped bamboo chips were placed in a polytetrafluoroethylene-lined hydrothermal reactor, deionized water was added, the temperature was raised to 180°C, and the reaction was carried out for 6 hours. After cooling, the materials were washed and dried.
[0065] Subsequent heat treatment (first time): The material was evenly spread in a quartz boat, placed in a tube furnace, heated to 700°C with a nitrogen flow rate of 200 mL / min, maintained for 2 hours, and then cooled naturally to room temperature.
[0066] Second carbonization treatment: The material after the first heat treatment was put into the tube furnace again, the nitrogen flow rate was increased to 300 mL / min, the temperature was set to 800 °C, and maintained at this temperature for 4 h.
[0067] When the material is cooled to 500°C, a 5% H2 / 95% N2 mixed gas is introduced and the material is continued to cool to room temperature to improve the microstructure and surface chemical properties of the carbon material.
[0068] Surface modification: The double-layer carbonized material was surface modified according to the standard method. The material was soaked in 0.01 M catechol solution at room temperature for 2 hours and then dried in an oven at 100 °C for 1 hour to ensure stable attachment of the modified film.
[0069] The double-layer carbonization process significantly improves the graphitization degree, conductivity and thermal stability of carbon materials, making it particularly suitable for high-rate discharge lithium-ion battery applications. The process also effectively improves the interfacial electrochemical properties of electrode materials, reduces resistance growth during charge and discharge cycles, and improves the overall efficiency of the battery.
[0070] Table 1 Comparison table of experimental data of embodiment Performance Indicators Embodiment 1 Embodiment 2 Embodiment 3 Specific surface area (m² / g) 800 850 900 Electrical conductivity (S / cm) 1.2 2.0 2.5 Initial capacity (mAh / g) 350 370 390 Cycle stability (after 500 cycles, %) 85 90 92 Rate performance (capacity retention at 2C rate, % 75 80 85 Mechanical strength (MPa) 100 120 110 Graphitization degree (ID / IG) 0.95 0.90 0.85 Surface modification uniformity medium high high Thermal stability (structure retention at 800°C, %) 85 87 90 Specific surface area (m² / g): Preferred embodiment 2 exhibits the highest specific surface area, which means that it has more active sites, which helps to improve the capacity.
[0071] Electrical conductivity (S / cm): Preferred embodiment 2 has the best electrical conductivity, which indicates that the double-layer carbonization treatment effectively improves the electrical conductivity of the material, making it more suitable for high-rate discharge applications.
[0072] Initial capacity (mAh / g): The initial capacity of the preferred embodiment 2 is the highest, showing its significant advantage in energy storage performance.
[0073] Cyclic stability: Among the three embodiments, the preferred embodiment 2 performs best in terms of cyclic stability, indicating that it maintains good structure and performance during long-term cyclic use.
[0074] Rate performance: The preferred embodiment 2 has the highest capacity retention rate at high rate discharge, and is suitable for application scenarios that require fast charging and discharging.
[0075] Mechanical strength (MPa): The surface modification process of the preferred embodiment 1 enhances the mechanical strength of the material, making it suitable for use under conditions of high mechanical stress.
[0076] Graphitization degree (ID / IG): The graphitization degree of the preferred embodiment 2 is the highest, indicating that its carbon structure is more ordered, which is helpful to improve the electrical conductivity and thermal stability.
[0077] Surface modification uniformity: Preferred Examples 1 and 2 have high surface modification uniformity, indicating that they can achieve consistent surface properties over a large area.
[0078] Thermal stability: Preferred embodiment 2 has the highest thermal stability, demonstrating its ability to maintain structural integrity in a high temperature environment.
[0079] Comparative Example 1: This comparative example provides a traditional method, comprising the following steps: Step 1: Selection and pretreatment of biomass materials: Common sawdust is selected as the biomass raw material. The sawdust is washed to remove surface impurities and dirt, and then dried naturally in the sun until the moisture content is less than 10%.
[0080] Step 2: Direct carbonization treatment: The dried sawdust was directly placed in a carbonization furnace, and the temperature was raised to 600°C at a heating rate of 10°C per minute without a protective atmosphere, and maintained for 2 hours to carbonize the sawdust material.
[0081] After carbonization, the material is naturally cooled to room temperature to obtain carbonized wood chip material.
[0082] Step 3: Simple surface treatment: The carbonized wood chip material was exposed to air for 1 hour to form a natural oxide layer without additional chemical treatment or surface modification.
[0083] Step 4: Preparation of electrode materials: The carbonized material was mixed with conductive carbon black (Super P) and PVDF binder in a mass ratio of 8:1:1, N-methylpyrrolidone (NMP) solvent was added, stirred evenly, and coated on the copper foil current collector.
[0084] The coated electrode sheet is dried in air to form the negative electrode material of the lithium-ion battery.
[0085] Table 2 Comparative data table Performance Indicators Embodiment 1 Comparative Example 1 Specific surface area (m² / g) 800 450 Electrical conductivity (S / cm) 1.2 0.5 Initial capacity (mAh / g) 350 200 Cycle stability (after 500 cycles, %) 85 60 Rate performance (capacity retention at 2C rate, % 75 40 Mechanical strength (MPa) 100 80 Graphitization degree (ID / IG) 0..95 1.10 Surface modification uniformity medium Low Thermal stability (structure retention at 800°C, %) 85 70 Specific surface area (m² / g): The specific surface area produced by traditional processes is low, which leads to insufficient active sites of the material and affects the capacity of the battery.
[0086] Conductivity (S / cm): The carbon materials used in traditional processes have poor conductivity, which results in high resistance and low efficiency of the battery during charging and discharging.
[0087] Initial capacity (mAh / g): The initial capacity of the conventional comparative example is significantly lower than that of Example 1, mainly due to insufficient carbonization treatment and low specific surface area.
[0088] Cycle stability: The cycle stability of traditional processes is poor, and the capacity decays rapidly during long-term use, which indicates that the material is prone to structural damage during repeated charge and discharge.
[0089] Rate performance: The conventional comparative example has a low capacity retention rate at high rate discharge and is not suitable for applications that require fast charging and discharging.
[0090] Mechanical strength (MPa): Due to the lack of optimized carbonization and surface treatment steps in the traditional process, the mechanical strength of the material is low and it is easy to be damaged during battery assembly and use.
[0091] Degree of graphitization (ID / IG): The carbon material produced by the conventional process has a low degree of graphitization, indicating that its structure is not as ordered as that of Example 1, and its conductivity and thermal stability are poor.
[0092] Surface modification uniformity: Traditional processes do not perform effective surface modification, resulting in uneven material surface properties, affecting the consistency and overall performance of the battery.
[0093] Thermal stability: The thermal stability of the conventional comparative example is poor, indicating that the material is prone to structural changes under high temperature conditions, affecting the safety of the battery.
[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a negative electrode material for a lithium-ion battery based on biomass materials, characterized in that: The following steps are involved: Step 1: pre-treating the biomass material, including washing and drying, to remove impurities and moisture; Step 2: using cellulase to perform enzymatic degradation on the pretreated biomass material to generate a porous structure material with a high specific surface area; Step 3: performing a nitrogen-sulfur dual doping reaction in the degraded biomass material, including using urea and sodium thiosulfate as doping sources and catalyzing the reaction with nitrase at 40-60° C.; Step 4: placing the doped material in a hydrothermal reactor at 180° C. for carbonization treatment to generate a nitrogen-sulfur dual-doped carbon material; Step 5: The carbonized material is subjected to subsequent heat treatment at 700°C for 2 hours in a nitrogen atmosphere to increase the degree of graphitization of the material; Step 6: Modify the surface of the heat-treated material to form a conductive film to obtain a negative electrode material for a lithium-ion battery.
2. The method for preparing anode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The biomass material is bamboo chips. Before the pretreatment step, the bamboo chips undergo the following treatment steps: a) Wash the bamboo shavings at least three times with deionized water, each time for no less than 20 minutes, to remove sand, dust and other impurities in the bamboo shavings; b) The washed bamboo chips are dehydrated through a filter, and then the dehydrated bamboo chips are placed in a hot air circulation oven at 60° C. and dried for 12 hours until the moisture content of the bamboo chips drops below 5%.
3. The method for preparing anode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The cellulase catalyzed degradation step comprises the following contents: a) preparing a 0.5% (w / w) cellulase solution, wherein the pH value of the solution is controlled between 5.5 and 6.5; b) mixing bamboo scraps and cellulase solution in a volume ratio of 1:1 to form a suspension, and performing an enzyme-catalyzed degradation reaction in a water bath at 30-40° C. for 24 hours; c) The suspension was stirred continuously at 300 rpm using a magnetic stirrer.
4. The method for preparing anode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The nitrogen-sulfur dual doping reaction comprises the following steps: a) Prepare 0.1 mol / L urea solution and 0.1 mol / L sodium thiosulfate solution, and mix the two solutions in a volume ratio of 1:1; b) mixing the mixed solution with the degraded bamboo shavings suspension at a volume ratio of 1:1, and adding 0.2% (w / w) nitrification enzyme to catalyze the decomposition of urea and release amino groups for nitrogen doping; c) performing a dual doping reaction at 40-60° C. for 12 hours, and maintaining a stirring speed of 200-300 rpm during the reaction to ensure uniformity of doping; d) After the reaction is completed, the suspension is quickly cooled to room temperature in an ice water bath and then washed with deionized water until the pH value of the washing solution is neutral.
5. The method for preparing anode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The hydrothermal carbonization step comprises the following: a) placing the biomass material after nitrogen-sulfur dual doping treatment in a hydrothermal reactor lined with high-purity polytetrafluoroethylene, adding deionized water so that the volume of water is 3-5 times the volume of the material; b) slowly raising the temperature of the reactor to 180°C at a rate of 5°C per minute and maintaining the temperature for 6 hours; c) After the reaction is completed, the heating source is turned off, the reactor is allowed to cool naturally to room temperature, the carbonized material is taken out, washed with deionized water until the filtrate is colorless and transparent, and dried in an oven at 80°C for 24 hours.
6. The method for preparing anode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The subsequent heat treatment steps include the following: a) Spread the dried material evenly in a quartz boat, place it in the heating zone of a tube furnace, and turn on nitrogen protection with a nitrogen flow rate of 200 mL / min; b) heating the material to 700°C at a heating rate of 5°C / min and maintaining it at this temperature for 2 hours; c) After the insulation is completed, cut off the heating source and continue to flow nitrogen until the furnace temperature drops to room temperature.
7. The method for preparing negative electrode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The surface modification step comprises the following: a) soaking the heat-treated carbon material in a 0.01 M catechol solution at room temperature for 2 hours to form a conductive film; b) After soaking, take out the material and dry it in an oven at 100°C for 1 hour.
8. The method for preparing negative electrode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The preparation steps of electrode materials include: a) mixing the heat-treated and surface-modified carbon material, Super P conductive carbon black and PVDF binder in a mass ratio of 8:1:1; b) adding N-methylpyrrolidone (NMP) to the mixture and stirring the mixture at a speed of 500 rpm for 12 hours using a high-speed stirrer until a uniform slurry is formed; c) using an automatic knife coater to evenly coat the slurry on a copper foil current collector with a thickness of 15 µm, and the coating thickness is controlled at 100 µm; d) The coated electrode was dried in a vacuum environment at 120°C for 12 h.
9. The method for preparing negative electrode materials for lithium-ion batteries based on biomass materials according to claim 1, characterized in that: The coated electrode sheets are processed through the following steps: a) using a hot press to press the electrode sheet at a pressure of 10 MPa for 2 minutes to obtain an electrode sheet with uniform thickness; b) Use a high-precision mold to cut the pressed electrode sheet into discs with a diameter of 14 mm.
Citation Information
Patent Citations
Graphene powder, method for producing graphene powder and electrode for lithium ion battery containing graphene powder
CN104271497A
Preparation method for biomass-based nitrogen-doped thin layer graphitized carbon material
CN108285143A
A nitrogen-doped 3D porous carbon material and a preparation method and application thereof
CN109037704A
Preparation method of nitrogen and / or sulfur modified three-dimensional porous carbon material
CN114804096A
Biomass nitrogen-sulfur or nitrogen-phosphorus double-doped activated carbon material for battery negative electrode material and preparation method of biomass nitrogen-sulfur or nitrogen-phosphorus double-doped activated carbon material
CN115159522A
Cited By
Preparation method of graphite negative electrode material for lithium ion battery, lithium ion battery, energy storage device and electric equipment
CN120208220A